2017
DOI: 10.1186/s12885-017-3776-5
|View full text |Cite
|
Sign up to set email alerts
|

Robust expression of tumor suppressor miRNA’s let-7 and miR-195 detected in plasma of Saudi female breast cancer patients

Abstract: BackgroundFemale breast cancer is frequently diagnosed at a later stage and the leading cause of cancer deaths world-wide. Levels of cell-free circulating microRNAs (miRNAs) can potentially be used as biomarkers to measure disease progression in breast cancer patients in a non-invasive way and are therefore of high clinical value.MethodsUsing quantitative RT-PCR, circulating miRNAs were measured in blood samples collected from disease-free individuals (n = 34), triple-negative breast tumours (TNBC) (n = 36) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 63 publications
3
63
0
Order By: Relevance
“…For example, miR-92a was found to be overexpressed in hepatocellular carcinoma tissues and to promote cancer cell proliferation, whereas its levels were decreased in the plasma of patients with hepatocellular carcinoma as relative to healthy individuals (Shigoka et al, 2010). Similarly, the tumor suppressors let-7 and miR-195 were undetectable in breast cancer tissues, whereas they were elevated in breast cancer patient plasma (Qattan et al, 2017). Thus, it can be seen that circulating miRNA levels do not necessarily reflect their tissue levels and functional roles (Cookson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-92a was found to be overexpressed in hepatocellular carcinoma tissues and to promote cancer cell proliferation, whereas its levels were decreased in the plasma of patients with hepatocellular carcinoma as relative to healthy individuals (Shigoka et al, 2010). Similarly, the tumor suppressors let-7 and miR-195 were undetectable in breast cancer tissues, whereas they were elevated in breast cancer patient plasma (Qattan et al, 2017). Thus, it can be seen that circulating miRNA levels do not necessarily reflect their tissue levels and functional roles (Cookson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among these candidates, miR-195 was of interest in this research owing to its tumor suppressive role in a series of human cancers, such as breast cancer, bladder cancer and prostate cancer. [28][29][30] Subsequently, we rstly validated that ZFAS1 directly targeted miR-195 and inhibited miR-195 expression. Previous researches reported that miR-195 signicantly alleviated cancer cell resistance to chemotherapy in colorectal cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to upregulation of oncogenic miRNAs, tumor suppressor Let-7c was decreased in BC tissue and sera according to a study performed in China (n = 90 BC, n = 64 controls) [103]. Although some studies have suggested that let-7 and miR-195 restoration may be therapeutic, results of Qattan et al in 2017 [104] supported literature indicating that tumor cells export hsa-miR-195 and let-7 miRNAs. While the data of this study did not generally support the use of these miRNAs as therapies, it suggested that these markers may be the most robust markers to use in a blood-based screen for the early detection of TNBC and luminal breast cancer [104].…”
Section: Mirnas As Breast Cancer Biomarkersmentioning
confidence: 89%
“…Although some studies have suggested that let-7 and miR-195 restoration may be therapeutic, results of Qattan et al in 2017 [104] supported literature indicating that tumor cells export hsa-miR-195 and let-7 miRNAs. While the data of this study did not generally support the use of these miRNAs as therapies, it suggested that these markers may be the most robust markers to use in a blood-based screen for the early detection of TNBC and luminal breast cancer [104]. The definition of a prognostic biomarker is one that indicates recurrence or progression; such as chance of survival, independent of the course of therapy.…”
Section: Mirnas As Breast Cancer Biomarkersmentioning
confidence: 94%